Development of Problem Solving-Oriented Worksheet of Physics Learning In Senior High School - Kahar, Muhammad Syahrul; Wekke, Ismail Suardi; Layn, Muhamad Ruslan (Jurnal Ilmiah Pendidikan Fisika Al-Biruni, 2018)
This study aimed at identifying how did the improvement in the problem-solving ability of learners work in improving the ability of learners in constructing the materials obtained after the development of Learner’s Worksheet in classroom learning. This research used Research and Development (R & D) approach using the Kemp model. Data collections were done through problem-solving tests, validation analysis, and correlation test. The indicators of this study included the effectiveness of the developed learner’s worksheet and the increased ability of problem-solving that was seen from the learning results obtained. The results showed that the average increase in the learning outcomes of the learners was equal to 79.44 with a difference in the scores of learning outcomes where tcount = 32.806 > ttable = 1.734, with a significance level of 0.000. Also, the improvement of learning outcomes on the response of learners gives significant influence with a score of 0.338 with a significance level of 0.085. Based on these results the development, the problem-solving oriented students’ worksheet is declared valid and effective based on the results of validation tests by experts and the results of the implementation of classroom learning. These results impact the students’ learning outcomes. It is expected that in the learning process with different materials, the worksheet can be applied in improving students' ability to solve problems. It is suggested for a research to collaborate the worksheet with other models and, media that can be linked to the problem-solving aspects, so that in its implementation, students have the confidence to succeed, be more active, and interested in problem-solving given